Peran Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak - Yenni Khristiana; Enggar Galuh Pramesthi (Universitas Muhammadiyah Metro, 2020)
The purpose of this study is to provide empirical evidence about the effects of tax socialization, motor vehicle tax sanctions, and Samsat Drive-Thru systems on motor vehicle Taxpayers compliance in Bantul Samsat offices in Daerah Istimewa Yogyakarta in 2019. The population in this study were all motor vehicle taxpayers in Samsat Bantul as many as 449,610. Sampling with Slovin formula obtained as many as 100 respondents and the method of data collection using accidental sampling. The data used in this study are primary data, data collection using the questionnaire method. Data analysis methods used in this research are validity test, reliability test, descriptive statistical analysis, classic assumption test, and hypothesis test is multiple linear regression analysis, t-test, and coefficient of determination. The results of this study indicate that motor vehicle tax sanctions and Samsat Drive-Thru systems have a positive and significant effect on motor vehicle taxpayer compliance, while tax socialization has a positive and insignificant effect on motor vehicle taxpayer compliance.